Optimization of Bio-Additive Formulation Using Subang Citronellal, Clove, and Patchouli: Evaluation of Density, Power Output, and CO₂–O₂ Emissions - Rahmi Rahmawati; Fenny Aprilliani; Nur Muhammad Malikul Adil (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This research examined the potential of essential oil–based bio-additives derived from citronella, clove, and patchouli to enhance the physicochemical properties, engine performance, and emission characteristics of Pertalite fuel. The study utilized Response Surface Methodology (RSM) with a Central Composite Design (CCD) to assess additive concentrations between 0.1 and 0.3 mL per liter of Pertalite. Findings indicated that these low-level additions did not significantly affect density, which remained similar to pure Pertalite. Likewise, power output and exhaust emissions (CO2 and O2) showed no notable improvements. Statistical evaluation using Design Expert® revealed all regression models were non-significant (p > 0.05), and optimization attempts failed to identify a valid optimum, with desirability values below 0.5. The minimal impact is attributed to the very low additive dosage, insufficient to influence atomization, combustion, or emission reduction. Additionally, gasoline’s non-polar nature limits sensitivity to parameters such as pH, while operational variations during engine testing (temperature, RPM, and load) may have masked minor effects. In summary, essential oil bio-additives at concentrations below 0.03% by volume are ineffective for measurable improvements. Future studies should investigate higher concentrations, purification of active compounds, improved blending techniques, and stricter engine testing protocols. The contribution of oxygenated compounds to combustion enhancement also merits further exploration.